2019
DOI: 10.2147/cmar.s200126
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic analysis of patients with mutant and wild-type <em>EGFR</em> gene lung adenocarcinoma</p>

Abstract: Purpose The purpose of this study was to investigate the relationship between epidermal growth factor receptor ( EGFR ) gene mutation and clinicopathological features of lung adenocarcinoma, and the prognostic and therapeutic value of EGFR . Methods EGFR gene mutations were detected in 424 patients with lung adenocarcinoma by amplification refractory mutation system (ARMS). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Moreover, our results also demonstrated that EGFR mutation was combined with better treatment response and PFS, which might be associated with the therapeutic efficacy of second-generation or third-generation EGFR-TKI. 66 In contrast, patients without EGFR mutation may not benefit from EGFR-TKI, thus resulting in a higher rate of SD and PD. There was no significant difference in OS, however, which may be affected by the short follow-up period in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results also demonstrated that EGFR mutation was combined with better treatment response and PFS, which might be associated with the therapeutic efficacy of second-generation or third-generation EGFR-TKI. 66 In contrast, patients without EGFR mutation may not benefit from EGFR-TKI, thus resulting in a higher rate of SD and PD. There was no significant difference in OS, however, which may be affected by the short follow-up period in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have tumors harboring one of these two mutations exhibit a greater objective response rate to afatinib, erlotinib, and gefitinib (10). There is differential prognosis based on EGFR mutation: the overall survival time for patients with exon-19 and -21 mutations with targeted therapy was found to be 41 to 44 months, longer than those with exon-18 mutation (19 months) (11). Therefore, detection of specific EGFR mutations may be of interest in guiding the application of targeted therapy in lung adenocarcinoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, one of the most important advances for the therapy of non-small cell lung cancer (NSCLC) was the development of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) 2,3. EGFR mutations are detected in more than 50% of patients with the histological subtype of adenocarcinoma in East Asia 4,5. Among patients harboring an activating EGFR mutation, EGFR-TKIs significantly improve not only the patient’s quality of life,6 but also progression-free survival (PFS)79 and overall survival (OS)10 compared with platinum-based doublet chemotherapy.…”
Section: Introductionmentioning
confidence: 99%